2014
DOI: 10.1007/s40259-014-0113-2
|View full text |Cite|
|
Sign up to set email alerts
|

Vedolizumab: A Review of Its Use in Adult Patients with Moderately to Severely Active Ulcerative Colitis or Crohn’s Disease

Abstract: Vedolizumab (Entyvio™) is a humanized monoclonal antibody α4β7 integrin-receptor antagonist indicated for the treatment of adult patients with moderately to severely active ulcerative colitis or Crohn's disease. This article reviews the pharmacological properties of intravenous infusions of vedolizumab and its clinical efficacy in adult patients with these diseases. In phase III clinical trials, patients with ulcerative colitis had significantly higher rates of clinical response and clinical remission when tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
(104 reference statements)
0
6
0
1
Order By: Relevance
“… 58 The CD trials included the GEMINI II and GEMINI III, which showed mixed results of efficacy. 59 At week 6 in GEMINI II RCT, clinical remission was seen in 14.5% who received vedolizumab and 6.8% who received placebo and clinical response was seen in 31.4% who received vedolizumab and 25.7% who received placebo ( P =0.23). Among patients who responded to induction therapy, 39.0% and 36.4% of those who received vedolizumab 8- and 4-weekly, respectively, were in clinical remission at week 52% versus 21.6% of those who received placebo ( P <0.001 and 0.004, respectively, for the two vedolizumab groups versus placebo).…”
Section: Discussionmentioning
confidence: 95%
“… 58 The CD trials included the GEMINI II and GEMINI III, which showed mixed results of efficacy. 59 At week 6 in GEMINI II RCT, clinical remission was seen in 14.5% who received vedolizumab and 6.8% who received placebo and clinical response was seen in 31.4% who received vedolizumab and 25.7% who received placebo ( P =0.23). Among patients who responded to induction therapy, 39.0% and 36.4% of those who received vedolizumab 8- and 4-weekly, respectively, were in clinical remission at week 52% versus 21.6% of those who received placebo ( P <0.001 and 0.004, respectively, for the two vedolizumab groups versus placebo).…”
Section: Discussionmentioning
confidence: 95%
“… 1 Vedolizumab is a gut-selective, humanised monoclonal antibody targeting α 4 β 7 integrin. 2 3 Clinical studies have demonstrated a positive benefit-risk profile of vedolizumab in adult patients with moderately to severely active ulcerative colitis (UC) or Crohn's disease (CD). 4–6 No major differences in safety profiles were observed between placebo-treated and vedolizumab-treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Vedolizumab, a monoclonal antibody specifically targeting the α 4 β 7 integrin heterodimer, is a new treatment for moderately to severely active UC. 8 Distinct from TNF antagonists and thiopurines, vedolizumab selectively inhibits binding of the α 4 β 7 integrin to mucosal addressin cell adhesion molecule-1 [MAdCAM-1], which is preferentially expressed in the intestinal endothelium. 9 Blockade of the α 4 β 7 integrin-MAdCAM-1 interaction interferes with migration of inflammatory cells into the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%